Perlindungan Hukum Terhadap Jual Beli Tanah yang Dilakukan dengan Itikad Baik - Firman, Handy; Gunawan, Gunawan (Universitas Ekasakti, 2023)
Land transactions play a crucial role in social and financial aspects, particularly concerning property ownership. The integrity and good faith of involved parties in these transactions are pivotal in legal protection, especially in safeguarding well-intentioned buyers. This study aims to explore the legal framework, challenges, and outcomes regarding land transactions involving buyers with good intentions, focusing on Indonesian law. The objective is to examine the existing legal framework, challenges, and outcomes associated with such transactions to ensure fair and proper practices. This research adopts a normative approach, emphasizing an in-depth analysis of existing legal texts, court decisions related to cases involving buyers acting in good faith during land transactions, and relevant legal documents. The primary focus is on